Exploiting SQ4R Cooperative Learning Method to Enhance EFL Students’ Reading Comprehension - Ahmad Ridho Rojabi (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
This study was aimed at enhancing the ability of the thirty-six EFL students of the English Study Program at IAIN Jember in reading comprehension by exploiting the SQ4R method. To achieve the purpose, a collaborative classroom action research design was employed by following four stages: planning, implementing, observing, and reflecting. This study was implemented in two cycles, in which both the first cycle and the second cycle were carried out in two meetings. This method consists of five stages; survey, question, read, reflect, recite, and review. The steps of surveying and questioning were implemented in pre-reading, the steps of reading and reflecting were implemented in whilst-reading, while the steps of recite and review were implemented in post-reading. Overall, the study has revealed that the SQ4R method enhanced students’ reading comprehension as well as students’ participation in the classroom. Keywords: SQ4R, reading comprehension, classroom action research